2016
DOI: 10.1097/md.0000000000004170
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative single-photon emission computed tomography/computed tomography for technetium pertechnetate thyroid uptake measurement

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 15 publications
1
63
0
Order By: Relevance
“…The quantitative SPECT/CT protocol has been described in detail in the literature ( 16 ). First, the SPECT/CT scanner (NM/CT 670, GE Healthcare, Pittsburgh, PA, USA) equipped with low-energy high-resolution collimator was calibrated to the dose calibrator (CRC-15R, CAPINTEC, Ramsey, NJ, USA) that was used for measurement of the injected dose of Tc-99m pertechnetate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantitative SPECT/CT protocol has been described in detail in the literature ( 16 ). First, the SPECT/CT scanner (NM/CT 670, GE Healthcare, Pittsburgh, PA, USA) equipped with low-energy high-resolution collimator was calibrated to the dose calibrator (CRC-15R, CAPINTEC, Ramsey, NJ, USA) that was used for measurement of the injected dose of Tc-99m pertechnetate.…”
Section: Methodsmentioning
confidence: 99%
“…The calibration factor (the system sensitivity of the SPECT/CT scanner) was determined to be 10176 counts/sec/mCi for Tc-99m ( 15 ). Second, using the calibrated scanner, SPECT/CT was performed over the neck area 20 minutes after injection of Tc-99m pertechnetate (dose 5 mCi) ( 16 ). A planar anterior image was obtained for 1 minute before the SPECT/CT acquisition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice to use mrBTU values instead of mean related BTU values was due to the fact that mrBTU values allow a direct comparability between SPECT/CT images of different patients and compensate for inter‐ and intra‐patient variability. Maximal relative BTU values are highly reproducible and do not depend from the volume and location of the region of interest . In this study mrBTUs showed excellent ICC scores and should be used as standard for further studies concerning the comparison of the BTU distribution and intensity on SPECT/CT of different patients …”
Section: Discussionmentioning
confidence: 59%
“…Tc-pertechnetate thyroid uptake test can be carried out using different parameters such as hardware (thyroid uptake system or planar gamma camera), software (thigh or mediastinum for background activity correction, syringe activity or separate standard source for injected dose determination), injection dose (37-370 MBq = 1-10 mCi) and measurement time and duration. Because of its suboptimal reliability, 99m Tc-pertechnetate thyroid uptake test is useful only for differential diagnosis to distinguish conditions withextremely altered thyroid function, such as Grave's disease from destructive thyroiditis [27]. In the present study, it was shown that the results could be different depending upon objectto-pinhole distances during 99m Tc-pertechnetate and thyroid uptake.…”
Section: Mmentioning
confidence: 64%